On the genus Raphidrilus Monticelli, 1910 (Polychaeta: Ctenodrilidae) with description of two new species - Magalhães, Wagner F.; Bailey–Brock, Julie H.; Davenport, Jennifer S. (Zootaxa, 2011)
Raphidrilus harperi sp. nov., is described from the Gulf Intracoastal Waterway (GIWW) in Venice, Florida from sediments consisting of coarse sands and shell hash. Raphidrilus hawaiiensis sp. nov., is described from Oahu’s shallow waters and inhabits a successful invasive alga in Waikiki and sandy sediments adjacent to ocean outfalls in Barbers Point and Sand Island, off Honolulu. The genus Raphidrilus is emended, the distinctness between the genera Raricirrus and Raphidrilus is confirmed and keys to all recognized genera of Ctenodrilidae and species of Raphidrilus are given.